PERSONALITY VARIABLES ASSOCIATED TO BULLYING (AGGRESSORS VERSUS VICTIMS) IN 10 TO 15 YEARS OLD SCHOOLERS - Cerezo Ramírez, Fuensanta (Anales de Psicología / Annals of Psychology, 2001)
The present study sumarices the investigation that left us to confirm some personality variables associated for each side of bullying. The sample was of 315 students from 10 to 15. 36 bullies and 17 victims were detected by the questionaire Bull (Cerezo y Esteban, 1994), then they completed the Eysenck’s EPQ-J, the Rosenberg’s Self Esteem Inventory (Adap. by Cerezo 1996) and Silva and Martorell’s Socialization Batery BAS-3. Results demonstrated some significativity differences: Bullies score higher in Psychoticism, Sincerity and Leadership, meanwhile, victims do in Self-Control and Ansiety/Shy and assing Psychoticism as the discriminant dimension between both groups.